2009
DOI: 10.4172/jpb.1000067
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Detached Fronds from a Resurrection Plant Selaginella Bryopteris - Response to Dehydration and Rehydration

Abstract: Selaginella bryopteris (L.) Bak is a resurrection plant. Uniquely, its detached fronds have the ability to survive desiccation similar to that of the whole plant. In order to understand the mechanisms of desiccation tolerance, proteome studies were carried out in this plant using detached fronds to reveal proteins that were differentially expressed in response to dehydration and rehydration. There was not much difference in electrolyte leakage between control, dehydrated and rehydrated fronds. During dehydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…S. moellendorffii reached 25% RWC within 1 h, whereas S. lepidophylla required 4 h to reach this same point. This rate is similar to S. bryopteris , a related resurrection species that takes 6 h to lose 80–90% of its RWC (Deeba et al. , 2009; Pandey et al.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…S. moellendorffii reached 25% RWC within 1 h, whereas S. lepidophylla required 4 h to reach this same point. This rate is similar to S. bryopteris , a related resurrection species that takes 6 h to lose 80–90% of its RWC (Deeba et al. , 2009; Pandey et al.…”
Section: Resultssupporting
confidence: 58%
“…Several members of the Selaginella genus, including S. lepidophylla (Iturriaga et al. , 2006), Selaginella bryopteris (Deeba et al. , 2009) and Selaginella tamariscina (Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Uniquely, its detached fronds have the ability to survive in nearly complete desiccation similar to that of the whole plant. [ 17 18 ] Thus, in China some of these herbs are called longevity herbs and were thought to be beneficial for the human health. Studies have demonstrated that some Selaginella species have potent antitumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In dehydration: Chemical analysis shows that the herb contains hexoses and proteins [17,18] suggest that S. bryopteris, has about 250 proteins that expressed in response to dehydration.…”
Section: (9) In Improvement Of Learning and Memorymentioning
confidence: 99%